Penerapan Media E-Comic dalam Pendidikan Karakter Kejujuran pada Mata Pelajaran Pendidikan Kewarganegaraan di SDN 16 Kota Langsa - Ayu Nafira; Lhutfia Wahyu Safutri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education that combines honesty education into an important component of basic learning. This study aims to explain how the use of e-comic media can improve students' honesty in Citizenship (PKn) subjects at public elementary schools 16 in Langsa City. Qualitative methods were used, with limited observation of the learning process. E-comic media was chosen because it can convey moral values ​​visually and attractively for students. The findings of the study indicate that comics can encourage students' interest in learning PKn while instilling honesty values ​​contextually. Students find it easier to understand the meaning of honesty in daily routines because the characters and stories in e-comics help them learn. In conclusion, e-comics can be used well as an educational tool to instill honesty in elementary school students.